The Role of Mitochondria in Systemic Lupus Erythematosus: A Glimpse of Various Pathogenetic Mechanisms - Yang, Shi-Kun; Zhang, Hao-Ran; Shi, Shu-Peng; Zhu, Ying-Qiu; Song, Na; Dai, Qing; Zhang, Wei; Gui, Ming; Zhang, Hao (Current Medicinal Chemistry, 2020)
Background: Systemic Lupus Erythematosus (SLE) is a polysystem autoimmune disease that adversely affects human health. Various organs can be affected, including the kidney or brain. Traditional treatment methods for SLE primarily rely on glucocorticoids and immunosuppressors. Unfortunately, these therapeutic agents cannot prevent a high recurrence rate after SLE remission. Therefore, novel therapeutic targets are urgently required. Methods: A systematic search of the published literature regarding the abnormal structure and function of mitochondria in SLE and therapies targeting mitochondria was performed in several databases. Results: Accumulating evidence indicates that mitochondrial dysfunction plays important roles in the pathogenesis of SLE, including influencing mitochondrial DNA damage, mitochondrial dynamics change, abnormal mitochondrial biogenesis and energy metabolism, mitophagy, oxidative stress, inflammatory reactions, apoptosis and NETosis. Further investigation of mitochondrial pathophysiological roles will result in further clarification of SLE. Specific lupus-induced organ damage also exhibits characteristic mitochondrial changes. Conclusion: This review aimed to summarize the current research on the role of mitochondrial dysfunction in SLE, which will necessarily provide potential novel therapeutic targets for SLE.
Keywords: pathogenetic mechanisms